2011
DOI: 10.1097/ncn.0b013e31821a1651
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nursing E-Learning Systems Success Based on Information System Success Model

Abstract: E-learning is thought of as an innovative approach to enhance nurses' care service knowledge. Extensive research has provided rich information toward system development, courses design, and nurses' satisfaction with an e-learning system. However, a comprehensive view in understanding nursing e-learning system success is an important but less focused-on topic. The purpose of this research was to explore net benefits of nursing e-learning systems based on the updated DeLone and McLean's Information System Succes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 17 publications
0
10
0
1
Order By: Relevance
“…E-learning is recognised as a type of training that gives great independence and flexibility for studying [18], and moreover, this study shows positive results in terms of the knowledge acquired and satisfaction. For these reasons, the implementation of this course is justified from economic and organisational points of view.…”
Section: Discussionmentioning
confidence: 68%
“…E-learning is recognised as a type of training that gives great independence and flexibility for studying [18], and moreover, this study shows positive results in terms of the knowledge acquired and satisfaction. For these reasons, the implementation of this course is justified from economic and organisational points of view.…”
Section: Discussionmentioning
confidence: 68%
“…Budgets and policy statements should reflect commitment to the program. Seven authors agreed on the positive effect of planning, describing objectives and expectations, and placing these in a timeline to maximize efficiency [ 7 , 23 , 36 , 37 , 39 , 40 , 49 ]. Cook et al [ 50 ] identified potential barriers to implementation, and Olson et al [ 20 ] advised readers to develop a marketing plan for reaching end users.…”
Section: Resultsmentioning
confidence: 99%
“…This model measures the success of information systems by measuring six variables, including information quality, system quality, intention to use, user satisfaction, service quality and net benefits ( Figure 1 ). The success of a virtual medical education system is multidimensional and can be associated with system quality, information quality and service quality, which are the prerequisites of three other key structures, namely user satisfaction, intention to use and net benefits, which measure the effects of using the system after it is implemented 7 . The evaluation of the courses held is one of the most important tasks of any organization and this need is twice as important in universities as they are considered a hub for research.…”
Section: Introductionmentioning
confidence: 99%